(untitled) (Docentes 2.0 Journal, 2022)
The study of factual sciences, especially mathematics, has been considered a subject of great importance in the development and progress of humanity over time. The research is based on the action-research, humanistic paradigm, with a qualitative, descriptive, and exploratory approach. In this way, the research’s objective was to incorporate ICT tools for developing mathematical thinking and processes in first and second-grade students of the educational institution La Laguna of the Municipality of Los Santos, in the department of Santander, Colombia. The sample consisted of 15 students from grades 1 and 2 of primary school, and their selection was made under a type of non-probabilistic convenience sampling. The documentary analysis procedure was used, a process that allowed the search, selection, and compilation of 60 digital educational resources hosted on the web, structured into three categories; web pages, YouTube channels, and applications for mobile devices, open and free to use. On the other hand, a pedagogical proposal of a didactic nature was designed to integrate the digital educational resources collected. Among the main results obtained, it was found that there is currently a wide variety of web pages, applications, channels, and digital educational tools that serve as dynamic elements to support learning didactics and the teaching methods used by teachers. It was concluded that ICTs are fundamental tools in current education.